PERAN ORANG TUA DALAM MENGONTROL PENGGUNAAN GADJET ANAK SEBAGAI UPAYA PENCEGAHAN PERNIKAHAN DINI (Studi Kasus Di KUA Kecamatan Gudo Kabupaten Jombang) - Risky Hidayat Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Based on the field facts that researchers obtained from the KUA apparatus of Gudo District, Jombang Regency, that early marriage caused by pregnancy out of wedlock is indicated by excessive interaction of teenagers in Gudo District with the opposite sex, so to find out the existing facts the researchers formulated the problem into 2, namely First, what are the causes of early marriage in the KUA, Gudo District, Jombang Regency? secondly, what is the role of parents in preventing early marriage by controlling children's use of gadgets in the KUA, Gudo District, Jombang Regency? This research uses qualitative field methods, where the data obtained will be reduced using descriptive methods This research concludes that the first factors for early marriage in KUA, Gudo District, Jombang Regency are economic factors, family traditions of marrying at an early age, local customs, pregnancy out of wedlock which is caused by excessive use of gadgets with the opposite sex. So parents play an important role in preventing early marriage by first monitoring when using a gadget, accompanying them when using a gadget, checking what their child accesses on social media, giving threats if the child goes too far in using a gadget.